Hubungan Healthy Eating Index Dengan Kenaikan Berat Badan Ibu Selama Kehamilan Di Sumatera Barat - Hrlfina, Riska (Faculty of Medicine, Universitas Andalas, 2024)
AbstractObjective: To determine the association between the healthy eating index of pregnant women and maternal weight gain during pregnancy in West Sumatra.Methods: Research with a cross-sectional design in West Sumatra on 110 pregnant women.This research is an analysis of secondary data from the study